Perinatal cytogenetic discrepancy in a pregnancy with mosaic 45,X/46, XY at amniocentesis and a favorable outcome - Chih-Ping Chen; Chao-Yun Wu; Schu-Rern Chern; Shin-Wen Chen; Fang-Tzu Wu; Chen-Chi Lee; Yun-Yi Chen; Li-Feng Chen; Wayseen Wang (Elsevier, 2022)
Objective: We present perinatal cytogenetic discrepancy in a pregnancy with mosaic 45,X/46, XY at amniocentesis and a favorable outcome. Case report: A 38-year-old, primigravid woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 45,X[2]/46,XY[6]. Level II ultrasound at 20 weeks of gestation was unremarkable, and the fetus had normal male external genitalia. Following genetic counseling, the woman decided to continue the pregnancy. At 39 weeks of gestation, a healthy male baby was delivered with a body weight of 3410 g and a body length of 54.5 cm. The male external genital organs were normal. The cord blood had a karyotype of 46, XY (40/40 cells). The umbilical cord had a karyotype of 45,X[1]/46,XY[39]. During follow-up at age one month, his body weight was 4.4 Kg (15th-50th centile), and his body length was 56 cm (50th-85th centile). The infant was doing well. Interphase fluorescence in situ hybridization analysis on 100 buccal mucosal cells revealed no abnormal Y-deletion cell, and all cells contained one Y signal. Conclusion: Perinatal cytogenetic discrepancy may occur in the pregnancy with mosaic 45,X/46, XY at amniocentesis.